Perbezaan Kualiti Guru Pendidikan Islam Sekolah Menengah Kebangsaan Berdasarkan Jantina, Lokasi Sekolah Dan Kekerapan Menyertai Latihan Dalam Perkhidmatan - Noornajihan Ja‘afar; Ab. Halim Tamuri (Universiti Malaya, 2024)
This study was designed to examine the quality of teachers of Islamic Studies (TIS) in national secondary schools in Peninsular Malaysia. A research on the differences of TIS quality based on a number of demographic factors such gender, school location and the frequency of participating in-service training was also carried out. This study used a quantitative approach and the questionnaire was the main instrument. Multi stage cluster sampling technique was used to determine the sample. The sample size involved in this research were 544 TIS representing a population of 8562 TIS in national secondary schools in Peninsular Malaysia. The results show that TIS quality is at an excellent level (M = 4.32). t-Test analysis shows that there is a small difference for quality variables based on gender, the male TIS (M = 4.41) topped females TIS (M = 4.29). The school location had no influence on the quality of TIS. In addition, the frequency factor participating in-service training also did not make a difference to the quality of the TIS. In addition, findings of this study pose implications for policy and practice of teaching among TIS.